The role of the conservative christians in the US-Israel “special relationship” - Mohd Afandi, Salleh; Kamarulnizam, Abdullah; Mohd Fauzi, Abu-Hussin; Fadzli, Adam (Serials Publications, 2017)
The article analyses the role and influence of religious movements on the foreign policy of United States (US). In this regard, the study examines how American Conservative Christians have attempted to exert their influence on US foreign policy towards Israel especially during the George W. Bush presidency (2001-2009). Among others, we examine the issue of the “special relationship” between the US and Israel and the discussion explore the historical perspectives and theoretical debates behind that “special relationship”. The paper argues that, the American Conservative Christians’ religious beliefs can be considered as a profound factor in shaping their dynamic political activism in influencing US foreign policy towards Israel. In addition, the discussion contends that the supports that were extended by Conservative Christian movements to the State of Israel and Jewish people are a continuity of a long tradition in Conservative Christians religious traditions.